Enzymatic hydrolysis of non-animal proteins for improving nutritional and sensory properties of foods - da Silva, Ronivaldo Rodrigues [UNESP] (Hindawi, 2021)
Taste and aroma of foods are recognized properties that contribute to increasing food acceptance and consumption, and methods for improving these attributes are highly sought after. For this, natural compounds are widely investigated and include peptides from fungi and plant proteins, which are alternative sources of protein in vegan and vegetarian diets. According to the specificity of peptidases and the protein substrates, a variety of peptides can be produced from enzymatic hydrolysis, which is an important advantage compared with chemical hydrolysis. Therefore, the following article discusses the use of proteolytic enzymes to produce protein hydrolysate from nonanimal sources for improving the sensory properties and nutritional value of foods. Practical applications: The purpose of this letter is to discuss the use of proteolytic enzymes as an eco-friendly alternative to produce protein hydrolysate from nonanimal sources for improving the sensory properties and nutritional value of foods.
Keywords: amino acids; aroma; food; peptidases; proteases; taste